United with friendship and science - Faizova, R.S. (Право и государство, 2014)
The article is devoted to 55-year anniversary of Peoples Friendship University of Russia, its history and achievements. Founded as a University which plays a unique role in uniting people from different countries, Peoples Friendship University of Russia created great opportunities for international community for educating students of different cultures. Sharing personal experience the author shows how University succeeded in fulfilling its goals providing excellent education possibilities within the international friendship atmosphere.
Keywords: KAZGUU University; international level; cooperation; anniversary; competence; countries; Research Subject Categories::LAW/JURISPRUDENCE